2022
DOI: 10.30541/v55i4i-iipp.781-802
|View full text |Cite
|
Sign up to set email alerts
|

Does Fiscal Decentralisation Matter for Poverty and Income Inequality in Pakistan?

Abstract: This study endeavours to investigate the impact of fiscal decentralisation on the welfare concerns of poverty, and income inequality in Pakistan for the time period 1972 to 2013. In order to capture the multi-dimensional nature of fiscal decentralisation, three indicators are used namely; revenue decentralisation, expenditure decentralisation and composite decentralisation. Further, the role of institutional quality is also incorporated in apprehending the responsivene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 19 publications
3
6
0
Order By: Relevance
“…Since the state governments are closer to the masses and more knowledgeable of the need of the people than the federal government, they will as a result carry out expenditures that have positive impact on welfare in both the short and long term. This finding is also in consistent with Francisco and Canare (2018), though contrary to Banwo (2012) and Shahzad and Yasmin (2016). Besides, the fact that the federal government is not closer to the people, a further reason why increases in the proportion of federal government expenditures failed in poverty reduction, is the high level of corruption at the federal or central government and diversion of funds from welfare improving expenditures.…”
Section: Ardl Long-run and Ecm Estimation Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…Since the state governments are closer to the masses and more knowledgeable of the need of the people than the federal government, they will as a result carry out expenditures that have positive impact on welfare in both the short and long term. This finding is also in consistent with Francisco and Canare (2018), though contrary to Banwo (2012) and Shahzad and Yasmin (2016). Besides, the fact that the federal government is not closer to the people, a further reason why increases in the proportion of federal government expenditures failed in poverty reduction, is the high level of corruption at the federal or central government and diversion of funds from welfare improving expenditures.…”
Section: Ardl Long-run and Ecm Estimation Resultssupporting
confidence: 71%
“…Using GMM estimate over a data period from 1973 to 2013, Shahzad and Yasmin (2016) found fiscal decentralization (expenditure and revenue decentralization) to be having an increasing impact on poverty in Pakistan in the absence of better institutional quality. The study of Banwo (2012) conducted on Nigeria found different impacts of fiscal decentralization indicators on poverty incidence in Nigeria.…”
Section: Brief Review Of Relevant Literaturementioning
confidence: 99%
“…Since, the state governments are closer to the masses and more knowledgeable of the need of the people than the federal government, they will as a result carry out expenditures that have positive impact on welfare in both the short and long-term. This finding is also in consistent with Francisco and Canare (2018), though Contrary to Banwo (2012) and Shahzad and Yasmin (2016). Beside the federal government not closer to the people, a further reason why increases in the proportion of federal government expenditure fail in poverty reduction is high level of corruption in the federal or central government and diversion of funds from welfare improving expenditures.…”
Section: Unit Root Stationarity and Cointegration Testssupporting
confidence: 84%
“…The study argued that this situation arises due to the crowding out effect of private consumption, and a negative wealth effect induced by increased government expenditure. Celikay and Gumus 2017 Using GMM estimate over a data period from 1973 to 2013, Shahzad and Yasmin (2016) found fiscal decentralization to be having an increasing effect on poverty in Pakistan. The study shows that one-unit increase in expenditure decentralization lead to 2.7 percent increase in poverty, whereas for revenue decentralization poverty increases by 0.…”
Section: Federalism Structure and Government Expenditure Trend In Nigmentioning
confidence: 99%
“…There are several studies fiscal decentralization effect on economic growth, poverty reduction, and income inequality in various contexts, both in developed and developing countries (Oates, 1972;Prud'homme, 1995;Tanzi, 2000;Rodriguez-Pose and Gill, 2004;Arze et al, 2005;Ezcurra and Rodriguez-Pose, 2009;Sepulveda and Martinez-Vazquez, 2011;Tselios et al, 2011;Ali et al, 2012;Gadenne and Singhal, 2014;Cavusoglu and Dincer, 2015;Ostwald et al, 2016;Shahzad and Yasmin, 2016;Dwicaksono and Fox, 2018 ). Fiscal decentralization can improve welfare of the people in the regions through increasing regional income (both from transfer funds and PAD), improving services to the community, building facilities and infrastructure, and providing targeted assistance to the poor (Gadenne and Singhal, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%